Association between oxidative balance score, systemic inflammatory response index, and cardiovascular disease risk: a cross-sectional analysis based on NHANES 2007–2018 data - Chen, Kai; Li, Senlin; Xie, Zhipeng; Liu, Yingjian; Li, Yangchen; Mai, Jinxia; Lai, Chengyang; Wu, Qili; Zhong, Shilong (Frontiers in Nutrition, 2024)
There is limited research on the relationship between Systemic Oxidative Stress (SOS) status and inflammatory indices. Adding onto existing literature, this study aimed to examine the association between dietary Oxidative Balance Score (OBS) and lifestyle OBS (which make up the overall OBS), and Cardiovascular Disease (CVD) prevalence at different Systemic Immune Inflammation Index (SII) and Systemic Inflammatory Response Index (SIRI) levels. This study involved 9451 subjects selected from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. The OBS comprised 20 dietary and lifestyle factors. Statistical methods included Weighted Linear Regression Analysis (WLRA), Logistic Regression Analysis (LRA), Sensitivity Analysis (SA), and Restricted Cubic Spline (RCS) analysis.The multivariate WLRA revealed that OBS was significantly negatively correlated with both SII (β=-5.36, p <0.001)and SIRI(β=-0.013, p <0.001)levels. In SA, removing any single OBS component had no significant effect on the WLRA results of SII and SIRI. Further subgroup analyses revealed that OBS was more impactful in lowering SII in women than in men. Additionally, OBS was more significantly negatively correlated with SII and SIRI in the low-age group than in the high-age group. Moreover, RCS analysis confirmed this linear relationship. Compared to dietary OBS, lifestyle OBS exerted a more significant effect on Coronary Artery Disease (CAD) (OR: 0.794, p=0.002), hypertension (OR: 0.738, p<0.001), Congestive Heart Failure (CHF) (OR: 0.736, p=0.005), Myocardial Infarction (MI) (OR: 0.785, p=0.002), and stroke (OR: 0.807, p=0.029) prevalence. Furthermore, SIRI exhibited a significant interaction in the relationship between overall OBS, dietary OBS, and CHF (P for interaction<0.001). On the other hand, SII had a significant interaction in the relationship between overall OBS, dietary OBS, and MI (P for interaction<0.05).OBS, including lifestyle and dietary OBS, were significantly negatively associated with SII and SIRI. Higher lifestyle OBS was associated with reduced risks of CAD, hypertension, CHF, MI, and stroke.